The calibration of the Sudbury Neutrino Observatory using uniformly distributed radioactive sources - Boudjemline, K; Cai, B; Cleveland, B; Evans, H; Ewan, G; Farine, J; Ford, R; Guillian, E; Hallin, A; Hallman, E; Howard, C; Jagam, P; et al. (2010)
The production and analysis of distributed sources of 24Na and 222Rn in the Sudbury Neutrino Observatory (SNO) are described. These unique sources provided accurate calibrations of the response to neutrons, produced through photodisintegration of the deuterons in the heavy water target, and to low energy betas and gammas. The application of these sources in determining the neutron detection efficiency and response of the 3He proportional counter array, and the characteristics of background Cherenkov light from trace amounts of natural radioactivity is described. © 2010 Elsevier B.V. All rights reserved.